Compact Metasurface-Based Optical Pulse-Shaping Device - Geromel, René; Georgi, Philip; Protte, Maximilian; Lei, Shiwei; Bartley, Tim; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
Dispersion is present in every optical setup and is often an undesired effect, especially in nonlinear-optical experiments where ultrashort laser pulses are needed. Typically, bulky pulse compressors consisting of gratings or prisms are used to address this issue by precompensating the dispersion of the optical components. However, these devices are only able to compensate for a part of the dispersion (second-order dispersion). Here, we present a compact pulse-shaping device that uses plasmonic metasurfaces to apply an arbitrarily designed spectral phase delay allowing for a full dispersion control. Furthermore, with specific phase encodings, this device can be used to temporally reshape the incident laser pulses into more complex pulse forms such as a double pulse. We verify the performance of our device by using an SHG-FROG measurement setup together with a retrieval algorithm to extract the dispersion that our device applies to an incident laser pulse.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Impact of 3D Curvature on the Polarization Orientation in Non-Ising Domain Walls - Acevedo-Salas, Ulises; Croes, Boris; Zhang, Yide; Cregut, Olivier; Dorkenoo, Kokou Dodzi; Kirbus, Benjamin; Singh, Ekta; Beccard, Henrik; Rüsing, Michael; Eng, Lukas M.; Hertel, Riccardo; Eliseev, Eugene A.; et al. (Nano Letters)
Ferroelectric domain boundaries are quasi-two-dimensional functional interfaces with high prospects for nanoelectronic applications. Despite their reduced dimensionality, they can exhibit complex non-Ising polarization configurations and unexpected physical properties. Here, the impact of the three-dimensional (3D) curvature on the polarization profile of nominally uncharged 180° domain walls in LiNbO3 is studied using second-harmonic generation microscopy and 3D polarimetry analysis. Correlations between the domain-wall curvature and the variation of its internal polarization unfold in the form of modulations of the Néel-like character, which we attribute to the flexoelectric effect. While the Néel-like character originates mainly from the tilting of the domain wall, the internal polarization adjusts its orientation due to the synergetic upshot of dipolar and monopolar bound charges and their variation with the 3D curvature. Our results show that curved interfaces in solid crystals may offer a rich playground for tailoring nanoscale polar states.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Electron–Nuclear Coherent Coupling and Nuclear Spin Readout through Optically Polarized VB– Spin States in hBN - Murzakhanov, Fadis F.; Mamin, Georgy Vladimirovich; Orlinskii, Sergei Borisovich; Gerstmann, Uwe; Schmidt, Wolf Gero; Biktagirov, Timur; Aharonovich, Igor; Gottscholl, Andreas; Sperlich, Andreas; Dyakonov, Vladimir; Soltamov, Victor A. (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Nonlinear Imaging of Nanoscale Topological Corner States - Kruk, Sergey S.; Gao, Wenlong; Choi, Duk-Yong; Zentgraf, Thomas; Zhang, Shuang; Kivshar, Yuri (Nano Letters)
Topological states of light represent counterintuitive optical modes localized at boundaries of finite-size optical structures that originate from the properties of the bulk. Being defined by bulk properties, such boundary states are insensitive to certain types of perturbations, thus naturally enhancing robustness of photonic circuitries. Conventionally, the N-dimensional bulk modes correspond to (N – 1)-dimensional boundary states. The higher-order bulk-boundary correspondence relates N-dimensional bulk to boundary states with dimensionality reduced by more than 1. A special interest lies in miniaturization of such higher-order topological states to the nanoscale. Here, we realize nanoscale topological corner states in metasurfaces with C6-symmetric honeycomb lattices. We directly observe nanoscale topology-empowered edge and corner localizations of light and enhancement of light–matter interactions via a nonlinear imaging technique. Control of light at the nanoscale empowered by topology may facilitate miniaturization and on-chip integration of classical and quantum photonic devices.

Spin Polarization, Electron–Phonon Coupling, and Zero-Phonon Line of the NV Center in 3C-SiC - Jurgen von Bardeleben, Hans; Cantin, Jean-Louis; Gerstmann, Uwe; Schmidt, Wolf Gero; Biktagirov, Timur (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Anisotropic Ion Migration and Electronic Conduction in van der Waals Ferroelectric CuInP2S6 - Zhang, Dawei; Luo, Zheng-Dong; Yao, Yin; Schoenherr, Peggy; Sha, Chuhan; Pan, Ying; Sharma, Pankaj; Alexe, Marin; Seidel, Jan (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Nonlinear imaging with all-dielectric metasurfaces - Schlickriede, Christian; Kruk, Sergey S.; Wang, Lei; Sain, Basudeb; Kivshar, Yuri; Zentgraf, Thomas (Nano Letters)

Nonreciprocal Asymmetric Polarization Encryption by Layered Plasmonic Metasurfaces - Frese, Daniel; Wei, Qunshuo; Wang, Yongtian; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
As flexible optical devices that can manipulate the phase and amplitude of light, metasurfaces would clearly benefit from directional optical properties. However, single layer metasurface systems consisting of two-dimensional nanoparticle arrays exhibit only a weak spatial asymmetry perpendicular to the surface and therefore have mostly symmetric transmission features. Here, we present a metasurface design principle for nonreciprocal polarization encryption of holographic images. Our approach is based on a two-layer plasmonic metasurface design that introduces a local asymmetry and generates a bidirectional functionality with full phase and amplitude control of the transmitted light. The encoded hologram is designed to appear in a particular linear cross-polarization channel, while it is disappearing in the reverse propagation direction. Hence, layered metasurface systems can feature asymmetric transmission with full phase and amplitude control and therefore expand the design freedom in nanoscale optical devices toward asymmetric information processing and security features for anticounterfeiting applications.

Silicon metasurfaces for third harmonic geometric phase manipulation and multiplexed holography - Reineke, Bernhard; Sain, Basudeb; Zhao, Ruizhe; Carletti, Luca; Liu, Bingyi; Huang, Lingling; de Angelis, Costantino; Zentgraf, Thomas (Nano Letters)

Simultaneous Spectral and Spatial Modulation for Color Printing and Holography Using All-dielectric Metasurfaces - Wei, Qunshuo; Sain, Basudeb; Wang, Yongtian; Reineke, Bernhard; Li, Xiaowei; Huang, Lingling; Zentgraf, Thomas (Nano Letters)